Crossing the Tracks? : More on Trends in the Training of Male and Female Workers in Great Britain - Melanie K. Jones; Paul L. Latreille; Peter J. Sloane (Institute for the Study of Labor (IZA), 2004)
A small number of recent empirical studies for several countries has reported the intriguing finding that the ?advantage? previously enjoyed by men in respect of training incidence and reported in earlier work in the literature has been reversed. The present paper explores the sources of the gender differential in training incidence using Labour Force Survey data, updating previous U.K. studies and providing further insights into the above phenomenon. The results suggest that the greater part of the ?gap? typically relates to differences in characteristics, among which the most important relate to occupation, industry and sector (public/private).
Keywords: J7; J2; J1; 330; gender; training; decomposition analysis; Frauenbildung; Betriebliche Berufsausbildung; Geschlecht; Bildungsverhalten; Grossbritannien